Preconditions for Effectiveness of Motivational Strategies in ESL/EFL Classroom: A Literature Review - Rai, Pradeep (Rupantaran: A Multidisciplinary Journal, 2025)
Many teachers of English as a Second Language (ESL) or English as a Foreign Language (EFL) employ motivational strategies to help students learn more effectively. However, these strategies, despite being termed ‘motivational,’ do not always inspire genuine motivation among students. In light of this challenge, this literature-based study examines key preconditions necessary for the effectiveness of motivational strategies used by ESL/EFL teachers in their classrooms. Through thematic analysis, the study reviews relevant literature, including notable works by psycholinguists, published research articles, and related weblogs. It explores the concepts of motivation and motivational strategies within the ESL/EFL context, focusing on what makes these strategies impactful in the classroom. Findings indicate that factors such as student mood and attitude, cultural context, and linguistic comprehensibility are crucial for the success of teacher-driven motivational approaches. The study suggests further research to identify additional preconditions that may influence the effectiveness of motivational strategies in English language classrooms. Identifying these preconditions is expected to help teachers, administrators, and policymakers plan and apply motivational strategies more effectively, thereby enhancing learning outcomes of English language learners.